2017
DOI: 10.1097/sih.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Task Trainer for Penile Corpus Cavernosa Aspiration

Abstract: Introduction Priapism is a rare yet time sensitive emergency with potentially significant morbidity. A novel task trainer was developed for corpus cavernosa aspiration and phenylephrine injection. The primary aim of this study was to assess model realism and usefulness for emergency medicine resident procedural education. Secondarily, an assessment of comfort level with the procedure before and after intervention was performed. Methods A priapism model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…As we discussed, our model was inspired by a previous model from Ruest et al [ 9 ]. The authors used a similar, but hollow phallic model with larger penrose drains for the corpora cavernosa, as well as the corpus spongiosum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we discussed, our model was inspired by a previous model from Ruest et al [ 9 ]. The authors used a similar, but hollow phallic model with larger penrose drains for the corpora cavernosa, as well as the corpus spongiosum.…”
Section: Discussionmentioning
confidence: 99%
“…The general design was inspired by previous work from Ruest et al, who used a condom trainer and penrose drains to build a more elaborate trainer [ 9 ]. The condom trainers used in their study were too cost-prohibitive for our design, so a more simple, less expensive condom trainer was used for our design.…”
Section: Methodsmentioning
confidence: 99%
“…It is was found that is realistic and useful for resident education. The use of the model in a simulation session can improve resident comfort in performing corpus cavernosa aspiration and phenylephrine injection (35).…”
Section: Non Surgical Optionsmentioning
confidence: 99%
“…Despite this, higher fidelity simulation may be more appropriate for advanced learners to give an adequate level of psychological fidelity. Whilst there are many commercially available simulators, high- and low-fidelity simulators, particularly for procedural skills, can be created from readily accessible material, such as gelatine-based and 3D printing, at low cost [ 11 , 13 , 19 , 55 , 56 ].…”
Section: Sbpt Blueprintmentioning
confidence: 99%